Analisa Dan Perbandingan Sistem Aplikasi Diagnosa Penyakit Asma Dengan Algoritma Certainty Factor Dan Algoritma Decision Tree Berbasis Android - Ratama, Niki (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
A computer is a tool that become the needs of society, both in the society in general, educational institutions, industry and even in the world of health, in the issue of health scope using technology, there are several cases that can be implemented, one of which is knowledge. Knowledge is a science that a person has acquired where the knowledge takes a long time to get it, sometimes someone with knowledge needs to store that knowledge, there are many methods in storing knowledge, from noting to books, videos and even giving it to someone else, but the method takes a long time, the expert system can be one solution in the knowledge where the expert system is a system that can be incorporated knowledge and store knowledge in the system, there are many expert system methods such as expert system method using Certainty Factor algorithm and algorithm Decision Tree. In the problem taken is to analyze, where asthma disease is the five largest disease that causes death in the world that varies between 6-30% (around 16.5%). In making the system using the waterfall model procedure and the program created using web display for admin management and display android device for user interface, the purpose of which is done in this research is with the application of expert systems and artificial intelligence, users or community will be knowing way and first handling in overcoming the asthma disease where the implementation of applications based on android smartphone, which can be used anywhere.